Fault identification in underwater vehicle thrusters via sliding mode observers - Zuev, Alexander; Zhirabok, Alexey; Filaretov, Vladimir (Zielona Góra: Uniwersytet Zielonogórski)
The paper is devoted to the problem of increasing the efficiency of underwater vehicles by using a fault diagnosis system for their thrusters which provides detection, isolation, and identification of minor faults. To address the problem, a two-stage method is proposed.
Keywords: underwater vehicles; thrusters; fault identification; sliding mode observers